2018
DOI: 10.1007/s10877-018-0138-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of the MIRUS™ system for general anaesthesia during surgery: a comparison of isoflurane, sevoflurane and desflurane

Abstract: The MIRUS™ system enables automated end-expired control of volatile anaesthetics. The device is positioned between the Y-piece of the breathing system and the patient's airway. The system has been tested in vitro and to provide sedation in the ICU with end-expired concentrations up to 0.5 MAC. We describe its performance in a clinical setting with concentrations up to 1.0 MAC. In 63 ASA II-III patients undergoing elective hip or knee replacement surgery, the MIRUS™ was set to keep the end-expired desflurane, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Two studies investigated the VA consumption of MIRUS™ at 1.0 MAC. A benchmark study reported a DES consumption of 40 ml per hour to achieve a fraction of 6.0–6.6%, and a clinical trial revealed a threefold higher consumption for ISO and SEVO, as well as a one and a half times higher consumption for DES compared to our results during hip and knee replacement surgery (respiratory minute volume 6–7 l min −1 ) [5, 8]. These high consumptions can be explained by the fact that the reflection efficiency of the MIRUS™ is highest at expiratory VA fractions of about 0.2–1.0%, and thus, more VA gets lost at higher concentrations [5].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Two studies investigated the VA consumption of MIRUS™ at 1.0 MAC. A benchmark study reported a DES consumption of 40 ml per hour to achieve a fraction of 6.0–6.6%, and a clinical trial revealed a threefold higher consumption for ISO and SEVO, as well as a one and a half times higher consumption for DES compared to our results during hip and knee replacement surgery (respiratory minute volume 6–7 l min −1 ) [5, 8]. These high consumptions can be explained by the fact that the reflection efficiency of the MIRUS™ is highest at expiratory VA fractions of about 0.2–1.0%, and thus, more VA gets lost at higher concentrations [5].…”
Section: Discussionmentioning
confidence: 68%
“…Sample size calculation was conducted in g power (Heinrich-Heine-University, Dusseldorf, Germany) and is based on a pilot study investigating the VA consumption of MIRUS™ at 1.0 MAC during surgery [8]. Significantly different VA consumption rates of the three gases were reported with an estimated effect size of d = 3.56, which was transferred to the current study design.…”
Section: Methodsmentioning
confidence: 99%
“…The prerequisite for using the Anaesthetic Conserving Device (ACD) AnaConDa ® (Sedana Medical AB, Danderyd, Sweden) or the MIRUS TM system (TIM, Koblenz, Germany) depends on several clinical parameters (see Figure 1 ). If lung compliance is acceptable, and CO 2 can be reduced sufficiently, both types of systems are able to maintain spontaneous breathing[ 19 - 21 ]. However, if lung compliance is poor, reduction of dead space and active humidification is necessary, which can be facilitated by inhaled sedation via a circle breathing system[ 22 , 23 ].…”
Section: Administration Of Volatile Anesthetics During Ards Therapymentioning
confidence: 99%
“…the dead space. The volumetric dead space of the MIRUS TM system is 100 mL[ 19 ], whereas the volumetric dead space for the AnaConDa ® system ACD-100 is 100 mL and 50 mL for the ACD-50[ 23 ]. However, the ECMO system eliminates CO 2 effectively.…”
Section: Administration Of Volatile Anesthetics During Ecmo Therapymentioning
confidence: 99%
“…Option number one: use an ICU ventilator, and place a device between the endotracheal tube and patient that vaporizes agent at the Y-piece and minimizes waste by reflecting part of the exhaled agent back during the next inspiration using a charcoal filter (AnaConDa, Mirus) [3][4][5][6][7][8][9]; some loss is obligatory to allow the partial pressure to be decreased at a sufficiently rapid rate. Any device added at the patient-machine interface (= at the Y-piece of the breathing system) is bound to add resistance and/or dead space-and thus to increase the work of breathing.…”
mentioning
confidence: 99%